MASLAHAH AL-MURSALAH: AN ALTERNATIVE APPROACH TO LEGAL DEVELOPMENT OF INDONESIA LAW LABOR SYSTEM - Fakhrudin, Ali; Gunarto, Gunarto; Khisni, Akhmad (UIN Raden Mas Said Surakarta, 2020)
This study aims to offer an alternative approach to the implementation of the labor law system in Indonesia. With the approach of Islamic law and socio-legal research as its basic tools for analyzing the implementation of various labor law regulations, the results of the study show; first, various labor problems that arise at this time are caused by, among others, there is no common understanding yet on the concept of equal relationship between workers and employers, the lack of government political will in enforcing the rules, the low skills of labor, uncertainty of market mechanisms, uneven distribution of the worker, and the presence of foreign workers; second, the implementation of the labor system is still far away from the concept of fiqh ijarah; and third, the lack of work spirituality.